RIGHT TO EDUCATION ACT IMPLEMENTATION IN RURAL SECTOR: A STUDY. - Swagatika Nanda (International Journal of Research Science and Management, 2017)
Education is the backbone of a country. A country development through the development of the education system. Education is the key aspects of society. In the changing scenario the system of education also changed. Education is the fundamental right of every individual. Right to education act free to the elementary education. But in the rural areas this information cannot motivate to the child to reach the school. There are some implementation problems in this area. This study identifies the major issues and gives some recommendations